PERAN GURU DAN RELAWAN DALAM MENGEMBANGKAN MODEL PENDIDIKAN DI MTS PAKIS DESA GUNUNGLURAH, CILONGOK, BANYUMAS - Ningrum, Yuneta Puspita; Baharruddin, Nalfaridas (Jurnal Interaksi Sosiologi, 2023)
This study describes and explains the roles of teachers and volunteers in developing an educational model at MTs PAKIS Gununglurah Village, Cilongok District, Banyumas Regency. This study used a qualitative method with a descriptive qualitative approach so as to obtain data in accordance with the research objectives. The location of this research was carried out at MTs PAKIS, Gununglurah Village, Cilongok District, Banyumas Regency. Data collection methods used in this study were in-depth interviews, observation, and documentation. The research targets in this study were PAKIS MTs teachers and volunteers. Determination of research targets using purposive sampling technique. The results of research by teachers and volunteers at MTs PAKIS consider that education is important as a right that every child must receive and to build children's character. PAKIS MTs teachers and volunteers have an important role in the sustainability of PAKIS MTs and creating an educational model that fits the needs of the community. In developing the educational model at MTs PAKIS, teachers and volunteers encountered various obstacles originating from internal factors such as laziness, lack of understanding by parents about the importance of education, shortage of volunteers and problems in managing volunteers, as well as external factors such as difficulty in signaling to support learning. Efforts were made to overcome these obstacles by providing understanding to parents and students, picking up students whose homes are far from MTs PAKIS, uploading volunteer recruitment on social media, managing volunteers through volunteer groups. To overcome the problem of signal difficulties and limited ownership of communication equipment, PAKIS MTs teachers and volunteers outsmarted this by conducting handy talky learning, using communication devices in groups, and carrying out online exams on hills or forests to get a signal.